Perspektif Pendidikan Nasional - Suluh, Melkianus (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2018)
[Title: The National Education Perspective]. This paper aims to describe the fulfillment of quality educator resources, the concept of national education quality, and the role of education in shaping the character of the nation. This study uses a library research approach (Library Research) with steps (1) choosing research topics, (2) searching for supporting information, (3) determining the focus of research, (4) classifying supporting materials, (5) reading and making research notes , (6) review and enrich reading material, and (7) carry out source analysis. The data analysis technique used is descriptive analysis by concentrating on solutions or solving problems raised. The results of this study indicate (1) the fulfillment of professional educator resources is filled with conventional methods, namely through the awarding of the teaching profession through certification programs, while in innovative ways carried out through training activities, increasing teacher capacity through the provision of scholarship programs, and the introduction of teacher prefectures (2) the concept of national education quality is fulfilled with the implementation and achievement of eight national education standards; (3) education has the role of forming noble characters and personalities through attitude formation, by making affective domains as protectors for the skills and cognitive domains.